HUBUNGAN SANITASI LINGKUNGAN, PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT DENGAN KEJADIAN DEMAM BERDARAH DANGUE (DBD) DIWILAYAH KERJA PUSKESMAS BEBESEN KECAMATAN BEBESEN KABUPATEN ACEH TENGAH - Rika Andreani; Zulfikar; Andi Pratama Putra (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACT Dengue fever, as an environmental-based disease, is still a public health problem that currently requires attention, where dengue fever is caused by environmental sanitation conditions that do not meet health requirements. The aim of this research is the relationship between environmental sanitation, knowledge, attitudes and behavior of the community with the incidence of dengue hemorrhagic fever (DBD) in the work area of the Bebesen Community Health Center, Bebesen District, Central Aceh Regency. This research design uses analytical descriptive with a cross sectional study design. The samples taken were 55 respondents. With random sampling technique. This research was carried out in the Bebesen Health Center Work Area, Bebesen District, Central Aceh Regency from 04 August to 19 August 2024. Based on the results of statistical analysis using the Chi Squer test, it was obtained that there was a Pvalue of Environmental Sanitation Relationship (0.001, 0.002, 0.003 and 0 .00) with the incidence of dengue fever. P value = 0.001 <0.05 There is a relationship between public knowledge and the incidence of dengue fever. Pvalue = 0.003 < 0.05 There is a relationship between community attitudes and the incidence of dengue fever. Pvalue = 0.002 < 0.05, this shows that there is a relationship between community behavior and the incidence of dengue fever in the working area of Bebesen Community Health Center, Bebesen District, Central Aceh Regency. It is hoped that the community can play an active role in carrying out environmental sanitation cleanliness, especially in carrying out the eradication of mosquito nests in order to reduce the number of mosquito nests to a minimum. Maybe there is an opportunity for mosquitoes to nest and breed by draining, closing water reservoirs both outside and inside the house and burying/burning used items so that the dengue fever incident can be resolved. Keywords : Environmental Sanitation, Knowledge, Attitudes, DHF Incidence